Contribución al estudio de las encefalopatías traumáticas - Paredes, Víctor (1956)
We do not claim in this contribution, delving into the substance and doctrine of traumatic encephalopathy, complex and widely debated issue, the official story in several Congresses and encouragement also: our scholars, whose works are known by all. Our purpose is less ambitious, and perhaps less scientific, refers to the findings and conclusions of the various cases collected from 1950 to 1955 and clearly gives the heading, "contribution to the study of traumatic encephalopathy". We do not believe, however, be exempted from some nosographic considerations, for the sake of clarity in the presentation and especially to better understand each other in a field in which usually the same terms are designated heterogeneous conditions, and conversely a same state has different designations.